Shaking Table Test of a New Type Insulation Decorative Block Wall under Out-of-Plane Loading - Jian Wu; Yuan Yuan Lv; Shuai Shuai Yin; Qi Wang (Shock and Vibration)
In order to solve the problems of complex construction, poor weather resistance, and environmental pollution of conventional thermal insulation materials, this paper introduces a new type of insulation decorative block (IDB) filled with insulation materials. Different anchoring methods were adopted to study the influence of anchor bolts on the out-of-plane mechanical properties of IDB walls. The test results revealed that the anchor bolts could effectively prevent the appearance and development of cracks in the specimens. With the increase of anchor bolts, the acceleration and displacement of the IDB walls decreased. Compared to rectangular arrangement, the staggered pattern of anchor bolts could reduce the relative displacement and acceleration. The structural calculation of IDB walls was carried out to determine the number of anchor bolts at different heights, and design suggestions were given to improve the performance of IDB walls. The analysis and test results indicated that the IDB is suitable for application in engineering structures.